2012
DOI: 10.2141/jpsa.011101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Phylogeographic Analysis of Native Chicken Populations in Myanmar and Thailand

Abstract: Native chickens in Myanmar and Thailand have been being domesticated for generations and yielded a wide variety of chickens. The objective of the research is to analyze the genetic variation and relationships of native chicken populations in Myanmar and Thailand. A total number of 249 genomic DNA samples from a total nine populations including the commercial lines, were genotyped using 98 autosomal SNP markers. The average heterozygosity of each population was in the range of 0.181-0.262. The neighbor-joining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Additionally, their study stated that 81 (86.2%) and 76 (80.9%) out of 94 indels markers could be validated as polymorphic loci in dogs (n = 7) and wolves (n = 18), respectively ( Väli et al, 2008 ). The H E values of chickens native to Myanmar in the present study were similar to those obtained by SNPs in an earlier report by Riztyan et al (2012) . However, for Thai and Laotian native chicken populations, the H E values in the present study were higher than those obtained by SNPs and blood protein polymorphisms in earlier studies ( Okamoto et al, 1999 ; Riztyan et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, their study stated that 81 (86.2%) and 76 (80.9%) out of 94 indels markers could be validated as polymorphic loci in dogs (n = 7) and wolves (n = 18), respectively ( Väli et al, 2008 ). The H E values of chickens native to Myanmar in the present study were similar to those obtained by SNPs in an earlier report by Riztyan et al (2012) . However, for Thai and Laotian native chicken populations, the H E values in the present study were higher than those obtained by SNPs and blood protein polymorphisms in earlier studies ( Okamoto et al, 1999 ; Riztyan et al, 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…The H E values of chickens native to Myanmar in the present study were similar to those obtained by SNPs in an earlier report by Riztyan et al (2012) . However, for Thai and Laotian native chicken populations, the H E values in the present study were higher than those obtained by SNPs and blood protein polymorphisms in earlier studies ( Okamoto et al, 1999 ; Riztyan et al, 2012 ). The H E values of Myanmar native chickens were lower than those of the Thai and Laotian populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The genotype data from these samples was combined with our previous subset of data from domestic chickens (Riztyan et al, 2011(Riztyan et al, , 2012, which was composed of two groups, native chickens and commercial breeds of chickens. Genomic DNA was purified from these samples using the proteinase K and phenol-chloroform method (Sambrook et al, 1989).…”
Section: Dna Samplesmentioning
confidence: 99%
“…The SNP markers have been successfully used to perform the STRUCTURE analysis for the native chicken populations in Indonesia. Recently, we have demonstrated that the contribution of a certain number of assumed ancestral populations could be explained through the membership coefficients in the STRUCTURE analysis (Riztyan et al, 2012). Therefore, we expected that the SNP markers could reveal distinct ancestral relationships between RJF and domestic chickens.…”
Section: Introductionmentioning
confidence: 99%